Cochlear Implantation – Anesthesia Challenges - SHirgoska, Biljana; Dokoska, Marija; Kikerkov, Igor (Montenegrin Society of Anesthesiology and Intensive Care, 2023)
Cochlear implants are an acceptable therapeutic options for the patients with irreversible hearing loss. Congenital hearing loss affects 1 to 3 per 1000 newborns. The reason for deaf children is deaf-mutizm, and deaf-mutizm could be an isolated non-syndromic sesorineural hearing loss (N-SNHL), if the patient has problem associated only with the vestibulocochlear nerve, or syndromic sensor neural hearing loss, that appears with other medical symptoms, that make a syndrome. The term syndromic sesorineural hearing loss (SNHL) is used if a patient has hearing loss in addition to other medical abnormalities, like pigments in retina (retinitis pigments’ form), abnormal iodine metabolism associated with thyroid goiter (euthyreotic form) or cardiac arrhythmias (cardiac form). Approximately 80 percent of children with genetic hearing loss have isolated non-syndromic sensor neural hearing loss and 20 percent of children with genetic hearing loss have other associated findings (syndromic sesorineural hearing loss).1 Speaking about technical aspects, cochlear implants are extremely expensive computerized electric prostheses that partially replace the functions of the cochlea. The surgery is time consuming and complicated, and the anesthesia technique plays a crucial role in success of cochlear implant surgery. Preoperative anesthetic evaluation of the patients, no ma7er if they are pediatric or adult patients, is very important. But, pediatric patients could have various types of unrecognized symptoms, before surgery, that are very important from anesthetic point of view. University clinic for ear, nose and throat surgery in Skopje, start with cochlear implantation in 2007. Macedonian academy of sciences and arts, medical department, in coordination with our clinic, made a project about inherited deafness, and nowadays we have a map of inherited deafness in Republic of North Macedonia.
Keywords: cochlear implantation; preoperative anesthetic evaluation